Design and content of Baju Kurung Kedah / Balqis Lyana Maulad Hamzah - Maulad Hamzah, Balqis Lyana (2019)
The background of the study explains more about Baju Kurung Kedah and its history along with the issues involving the Baju Kurung Kedah. The problem statement is that Baju Kurung are not so popular to the young generation as they prefer to follow the trends of this era. This is due to the lack knowledge’s of our Baju Kurung and the Malay tradition. This study will help the younger generation to not ignore our traditional clothes. The significant of this study is will give more understanding about the Baju Kurung Kedah to the young generation. It is also included the research objectives which are to analyze the type of design of Baju Kurung Kedah and to interpret the content of Baju Kurung Kedah whereby both objectives answering the research questions for this study. In scope and limitation explains where the research is held for the Baju Kurung Kedah at several places such as the National Museum, the Department of National Heritage in Kuala Lumpur to gain information. Literature review consisting the literature reviews by writers in books, journals, as prove that the study is relevant. Moreover, methodology explains what method is used to complete this research. Qualitative method is used in this study by collecting data from books, journal, website and also by observing the current trend in this era. Analysis and findings on the Baju Kurung Kedah consist a table of analysis to explains what has been found by using formalistic theory such as the elements of art such as space, line, texture, colour and shape. The conclusion of the whole research is stated and recommendations to the younger generations from the age of 5 to 12 years old an application whereby it is an online game featuring the Baju Kurung Kedah. This application will help to give knowledge’s on our culture in Malaysia.